2009
DOI: 10.4103/0970-1591.52913
|View full text |Cite
|
Sign up to set email alerts
|

Seminal vesicle sparing laparoscopic radical prostatectomy using a low-energy source: Better continence and potency

Abstract: Objectives:Ongoing with the newer developments in laparoscopic radical prostatectomy (LRP), we report our experience in a consecutive series of 42 patients with a mean 18-month follow-up. We also studied the use of a low-energy source, especially in the region of the prostatic apex and the neurovascular bundle and evaluated its outcome on continence and potency.Materials and Methods:Between November 2003 and December 2008, 50 patients aged 50–80 yrs underwent LRP with vesicourethral anastomosis and of these, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Sectioning the seminal vesicles near the tip would create a larger margin away from the nearby pelvic nerves and theoretically improve continence. 28 Similarly, another study hypothesized that this modification would diminish damage to the NVB, and found superior preservation of continence (95% versus 28%), erectile function (drop of 5 versus 14.5 points on the International Index for Erectile Function (IIEF-5) score), and quality of orgasms (90% versus 62%) compared with the control group. 29 Some argue that the remaining seminal vesicle tissue produces prostate-specific antigen (PSA) and can compromise the validity of post-RP oncologic follow up.…”
Section: Seminal Vesicle Preservationmentioning
confidence: 99%
“…Sectioning the seminal vesicles near the tip would create a larger margin away from the nearby pelvic nerves and theoretically improve continence. 28 Similarly, another study hypothesized that this modification would diminish damage to the NVB, and found superior preservation of continence (95% versus 28%), erectile function (drop of 5 versus 14.5 points on the International Index for Erectile Function (IIEF-5) score), and quality of orgasms (90% versus 62%) compared with the control group. 29 Some argue that the remaining seminal vesicle tissue produces prostate-specific antigen (PSA) and can compromise the validity of post-RP oncologic follow up.…”
Section: Seminal Vesicle Preservationmentioning
confidence: 99%
“…The excision of neurovascular bundles causes more incontinence and impotence than when the neurovascular bundles are preserved. 19 To spare the prostatic neurovascular bundles, laparoscopic and robotic-assisted prostatectomy are both useful, 20 because magnification facilitates a more accurate dissection with less traction. 21 Surgically, a midline vertical incision is made into Denonvilliers' fascia—along the entire gland extending up the urethra—and the fascia is sharply retracted to the right and left to expose the posterior prostatic capsule.…”
Section: Introductionmentioning
confidence: 99%